Multi-omics analysis of parthanatos related molecular subgroup and prognostic model development in stomach adenocarcinoma - Xiangxin Wu; Lianming Cai; Yanping Liu; Bowen Wang; Tianyi Xia; Zhenhua Liu (PLoS ONE, 2025)
Stomach adenocarcinoma (STAD), the most prevalent histological subtype of gastric cancer, exhibits high heterogeneity and poor prognosis, posing significant therapeutic challenges. Parthanatos, a distinct form of regulated cell death mediated by poly (ADP-ribose) polymerase-1 (PARP-1), has been implicated in tumor biology and therapeutic resistance; however, the role of parthanatos-associated genes (PRGs) in STAD remains largely unexplored. In this study, we performed a comprehensive multi-omics analysis integrating transcriptomic, genomic, and clinical data from public databases to delineate the molecular landscape of PRGs in STAD. Unsupervised clustering revealed distinct PRG-related molecular subtypes with significant differences in clinical outcomes, immune infiltration profiles, and biological pathway activation. Based on machine learning algorithms, we established and validated a novel PRG-based prognostic signature, which demonstrated robust predictive performance. Moreover, single-cell RNA sequencing and in vitro functional assays were conducted to explore cellular heterogeneity and gene function. Notably, in vitro experiments, including western blot, colony formation, CCK-8, and Transwell assays, confirmed that one key PRG, COL8A1, promotes STAD cell proliferation and migration. Collectively, our findings highlight the clinical and biological significance of PRGs in STAD, offering novel biomarkers and potential therapeutic targets for STAD precision treatment.